Effect of temperature variation on shift and broadening of exciton band in Cs3Bi2I9 layered crystals - Machulin, V.F.; Motsnyi, F.V.; Peresh, E.Yu.; Smolanka, O.M.; Svechnikov, G.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The exciton reflection spectra of Cs3Bi2I9 layered crystals is investigated in the temperature region 4.2–300 K with light polarization E ⊥ c. It is estimated that the energy gap Eg equals 2.857 eV (T = 4.2 K) and the exciton binding energy Ry is 279 meV. A nontraditional temperature shift of Eg(T) for the layered substances is found for the first time. It is learned that this shift is described very well by the Varshni formula. A transition region in the temperature broadening of the half-width H(T) of the exciton band with the increase of temperature is registered in the interval between 150 and 220 K. It is shown that this region may be identified as the heterophase structure region where ferroelastic and paraelastic phases coexist. A surge of H(T) at the point of theferroelastic phase transition (Tc = 220 K) is also observed.